Synthesis of Fluorescent BODIPY‐Labeled Analogue of Miltefosine for Staining of Acanthamoeba. Issue 27 (16th July 2018) - Courrier, Emilie; Maret, Corentin; Charaoui‐Boukerzaza, Sana; Lambert, Victor; De Nicola, Antoinette; Muzuzu, Wenziz; Ulrich, Gilles; Raberin, Hélène; Flori, Pierre; Moine, Baptiste; He, Zhiguo; Gain, Philippe; et al.
Abstract: Amoebae pose a potential health risk as pathogenic agents i. e. in the central nervous system or the cornea, early diagnostics are important to implement rapid treatments and reduce impact on human health. Thus, development of selective fluorescent tags for Amoebae is an important issue. Analogues of Miltefosine, a drug effective against various strains of free‐living amoebae, have been synthesized. They are derivatives of the 11‐aminoundecylphosphocholine. Via a peptide bond, a strong emitting BODIPY was embedded to the structure. This compound (1) was used to selectively stain for Acanthamoeba castellanii . In order to test the effect of the insertion of the amide function in the alkylbackbone of this modified Miltefosine, a model molecule (2) was prepared by replacing the dye by the anisidyl moiety. Anti‐amoebic activity was evaluated for both. Abstract : A Fluorescent analogue of Miltefosine based on BODIPY derivative of the 11‐aminoundecylphosphocholine has been synthesized and its photophysical properties investigated. It presents a high brightness in aqueous media with an emission at 508 nm. This biomarker has been used in vitro to stain Acanthamoeba Castellanii . It specifically linked the cytoplasm and vacuoles of living Acanthamoeba trophozoites but not their nucleus and shows moderate cytoxicity.